Strategi Guru Dalam Meningkatkan Mutu Proses Pembelajaran di Era Covid-19 di SD GMIM I Wanga - Yulmi H. Mottoh (Peneliti.net, 2022)
This research was carried out with the aim of knowing teacher learning strategies for students in the Covid-19 era in class V SD I Wanga. In this researcher, the researcher uses a qualitative descriptive approach, according to Denzin & Lincoln (1994) stating that qualitative research is research that uses a natural setting with the intention of interpreting phenomena that occur and is carried out by involving various existing methods (Anggito & Setiawan, 2018). The method used by the researcher is contextual teaching and learning (CTL). According to Wina Sanjaya Contextual Teaching and Learning (CTL) is a learning strategy that emphasizes the process of full student involvement to be able to find the material being studied and relate it to real life situations. Based on the results of the research and discussion, it was concluded that the learning applied to the fifth grade students of SD GMIM I Wanga was an online learning series planning using learning approaches and models to achieve learning objectives. The learning approach is done by explaining the material through video. Students who go offline or offline study material from the LKS (student worksheets) that have been brought by each student. The learning method is that the teacher makes a video explaining the material and then sends it to students via WhatsApp. Online time allocation is done every day, while offline is determined independently or independently, and the collection of tasks is in accordance with the agreement of the teacher. The learning media used are photos or videos that are accessed from WhatsApp, then students collect their assignments via google meet and whatsapp. The material comes from student textbooks and worksheets and the material presented is in accordance with basic competencies, then the teacher makes questions as learning evaluations.